Analisis Rasio Likuiditas dan Profitabilitas untuk Mengukur Kinerja Keuangan PT Gudang Garam Tbk Periode 2012-2022 - Ega Saputri J., Andriny; Oktrima, Bulan (Jurnal Disrupsi Bisnis, 2024)
This research aims to analyze the financial reports of PT Gudang Garam Tbk. Utilizing a quantitative research approach, the focus is on liquidity and profitability ratios. This study employs descriptive research, which is the process of gathering data and contrasting it with industry norms. Results of analysis and discussion of financial performance at PT Gudang Garam Tbk. measured using the liquidity ratio to financial performance consisting of the Current Ratio (CR) and Quick Ratio (QR) Cash Ratio (CSR) shows that the company's performance is not good in managing the company. The ratio of profitability to financial performance consisting of Return On Assets (ROA) is in the good category and Return On Equity (ROE) is in the poor category and Net Profit Margin shows it is in the good category.